Important Structural Linkages in the Process of Income Circulation Defined by SAMs - Tomaszewicz, Łucja (Comparative Economic Research. Central and Eastern Europe, 2014)
The main aim of this paper is to present the analytical possibilities offered by Social Accounting Matrices as regards economic policy. These matrices are synthetic presentations of income flows in the economy, described by the international statistical system - System of National Accounts (SNA). Comparative analyses presented in the paper are based on the structure of transactions observed in SNA for three years (2002, 2007, 2012) for selected countries (Germany, Spain, Poland, Bulgaria). The analysis includes a comparative study of the expenditure and income structure of individual institutional sectors, SAM multipliers as an important analytical tool, and the importance of SNA transactions, evaluated by how their changes influence multipliers.